2023
DOI: 10.1186/s10020-023-00607-8
|View full text |Cite
|
Sign up to set email alerts
|

An engineered miRNA PS-OMe miR130 inhibits acute lung injury by targeting eCIRP in sepsis

Abstract: Background Sepsis is caused by the dysregulated immune response due to an initial infection and results in significant morbidity and mortality in humans. Extracellular cold inducible RNA binding protein (eCIRP) is a novel mediator identified in sepsis. We have previously discovered that microRNA 130b-3p inhibits eCIRP mediated inflammation. As RNA mimics are very unstable in vivo, we hypothesize that an engineered miRNA 130b-3p mimic named PS-OMe miR130, improves stability of the miRNA by prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…However, given that any miRNA is unstable in vivo because of its susceptibility to degradation by nucleases, miRNA 130b-3p was chemically engineered in an in effort to improve its stability and thereby increase its potential efficacy (41). Recently, this modified miRNA, which we termed PS-OME miR130, has shown to reduce inflammation and tissue injury in mice, which underwent either hepatic I/R or cecal ligation puncture sepsis (19,20). It has been shown that using surface plasmon resonance and three-dimensional computational modeling, PS-OME miR130 retained its binding affinity to eCIRP and that the binding was comparable to that which was observed with the unmodified miRNA 130b-3p (19).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, given that any miRNA is unstable in vivo because of its susceptibility to degradation by nucleases, miRNA 130b-3p was chemically engineered in an in effort to improve its stability and thereby increase its potential efficacy (41). Recently, this modified miRNA, which we termed PS-OME miR130, has shown to reduce inflammation and tissue injury in mice, which underwent either hepatic I/R or cecal ligation puncture sepsis (19,20). It has been shown that using surface plasmon resonance and three-dimensional computational modeling, PS-OME miR130 retained its binding affinity to eCIRP and that the binding was comparable to that which was observed with the unmodified miRNA 130b-3p (19).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, this modified miRNA, which we termed PS-OME miR130, has shown to reduce inflammation and tissue injury in mice, which underwent either hepatic I/R or cecal ligation puncture sepsis (19,20). It has been shown that using surface plasmon resonance and three-dimensional computational modeling, PS-OME miR130 retained its binding affinity to eCIRP and that the binding was comparable to that which was observed with the unmodified miRNA 130b-3p (19). Importantly, studies on the half-life of the unmodified mimic were unsuccessful because it was undetectable in serum, whereas the modified miRNA was found to have a half-life of 277.2 min (18,19).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations